From 'home work' to 'home office work'?: Perpetuating discourses and use patterns of tele(home)work since the 1970s: historical and comparative social perspectives. (7th April 2023) - Homberg, Michael; Lükemann, Laura; Abendroth, Anja-Kristin
Abstract : In contemporary debates, it is regularly overlooked that working from home already has a long history, while the phenomenon of 'tele(home) working' has even gained momentum since the 1970s, being increasingly technologically enabled and socially prepared. This article aims to identify the self-perpetuation of work from home by investigating phases, turning points and diverging temporalities of gender- and parenthood-specific discourses and use patterns of tele(home)work in Germany and the United Kingdom from an interdisciplinary perspective, combining historical and comparative social analysis.